Liver Transplant in a Patient under Methylphenidate Therapy: A Case Report and Review of the Literature - Hoi Y. Tong; Carmen Díaz; Elena Collantes; Nicolás Medrano; Alberto M. Borobia; Paloma Jara; Elena Ramírez (Case Reports in Pediatrics)
Background. Methylphenidate (MPH) is widely used in treating children with attention-deficit-hyperactivity disorder. Hepatotoxicity is a rare phenomenon; only few cases are described with no liver failure. Case. We report on the case of a 12-year-old boy who received MPH for attention-deficit-hyperactivity disorder. Two months later the patient presented with signs and symptoms of hepatitis and MPH was discontinued, showing progressive worsening and developing liver failure and a liver transplantation was required. Other causes of liver failure were ruled out and the liver biopsy was suggestive of drug toxicity. Discussion. One rare adverse reaction of MPH is hepatotoxicity. The review of the literature shows few cases of liver injury attributed to MPH; all of them recovered after withdrawing the treatment. The probable mechanism of liver injury was MPH direct toxicity to hepatocytes. In order to establish the diagnosis of MPH-induced liver injury, we used CIOMS/RUCAM scale that led to an assessment of “possible” relationship. This report provides the first published case of acute MPH-induced liver failure with successful hepatic transplantation. Conclusions. It is important to know that hepatotoxicity can occur in patients with MPH treatment and monitoring the liver’s function is highly recommended.